Analisis Kepercayaan, Kenyamanan Dan Kemudahan Pelanggan Gojek Online Di Kota Malang - Nidya Rizkawati; Eny Rachmawati; Anti Ati Wijayanti (PRAGMATIS, 2022)
The increasing number of internet users in Indonesia can cause changes in people's mindsets in using transportation services. The development of this technology itself has influenced someone to create various kinds of new innovations which can easily connect customers who need transportation services with transportation service providers through online transportation service applications on smartphones. Gojek's online transportation service is now familiar to Indonesians. Almost all corners of both small and large cities can all use online motorcycle taxi services. But it should also be realized that this type of transportation service is not the only one. Therefore, this online gojek transportation service must also have ways to attract the sympathy of customers. So in this study will determine how much public trust in the use of online gojek services. This study aims to determine and analyze how much influence trust, convenience and comfort simultaneously on customer satisfaction using online transportation services Gojek in Malang City. The research method used in this research is OLS (Ordinary Least Square).. In this research, the population is all people in Malang City, users of online transportation, especially Gojek, so the number is unpredictable or infinite. The population and sample used were 96 respondents. The data analysis technique uses descriptive statistics and correlation analysis. The test results show that Trust, Convenience, and Ease have an effect on customer satisfaction together. While the partial hypothesis test shows that the factors of trust, comfort and convenience independently influence customer satisfaction.